The criminal act at the core of the nexus security-insecurity: a tentative approach to female crime - Frois, Catarina (Female Crime and Delinquency in Portugal: In and Out of the Criminal Justice System, 2018)
To what extent can we consider the criminal act as a strategy, a choice, a necessity, an opportunity or even the inevitable outcome in the individual struggle to deal with adversity, inequality, discrimination, fear or vulnerability—in short, as a way to obtain security? This is the working hypothesis developed in this chapter, offering an exploratory reflection around the nexus security–criminality, framed within the broader theoretical concept of human security with a specific focus on (failed) state interventions and its implications on female crime.